Evaluating flushing procedures to prevent drug carryover during medicated feed manufacturing - Martinez-Kawas, Adrian (Kansas State University, 2008)
Carryover of medicated feed additives between batches of feed can potentially result in harmful drug residues in the edible tissues of food-animals. Flushing the equipment with an ingredient, such as ground grain, is one method used to remove any residual medicated feed from the system. It is generally recommended that the quantity of flush used be between 5 and 10% of the mixer's capacity. However, there is little data that supports this recommendation. Therefore, two experiments were conducted to 1.)determine which manufacturing equipment is the major source of carryover, 2.)evaluate which flush size adequately prevents drug carryover, and 3.) quantify the interrelationship between flush size and drug concentration. In Experiment 1, feed medicated with nicarbazin (Nicarb 25%®; 0.0125%) was manufactured and conveyed from the mixer, through a drag conveyor and bucket elevator, and then into a finished product bin. The system was then flushed using ground corn in the amount of 2.5, 5, 10, 15, or 20% of the mixer's capacity (454.5 kg). Subsequently, a non-medicated diet was conveyed through the system and samples were collected and analyzed for nicarbazin. No significant (P > 0.05) differences were detected among the flush treatments, and all treatments were effective in preventing nicarbazin carryover to the non-medicated diet. In Experiment 2, feed medicated with three levels of monensin (Rumensin® 80; 100, 600, and 1,200 g/ton) was manufactured and handled in the same manner as in Experiment 1. The flushing treatments examined were: 1, 2.5, and 5% of the mixer's capacity. Samples of the non-medicated diet for each treatment were collected and analyzed for monensin. There was significant interaction (P < 0.05)between drug level and sampling location between treatments. As the drug level in the medicated diet increased, higher concentrations of monensin were detected in the non-medicated diet. Collectively, these studies demonstrate that a 2.5%, even a 1% flush size, is effective in preventing carryover of medicated feed additives. It was also demonstrated that the bucket elevator and finished product bin were the major sources of drug carryover in this particular feed manufacturing system.
Keywords: Feed manufacturing; Medicated feed; Drug carryover; Contamination; Flushing; Agriculture, Animal Culture and Nutrition (0475)